1,5-Benzodiazepin-2(3H)-ones: In Vitro Evaluation as Antiparkinsonian Agents - Ana Ortíz de Zárate; Marta Pérez-Torralba; Iñigo Bonet Isidro; Concepción López; Rosa M. Claramunt; Diana Martínez-Casanova; Isabel Sánchez-Vera; Jesús Jiménez-González; José Luis Lavandera (MDPI AG, 2021)
A new series of twenty-three 1,5-benzodiazepin-2(3H)-ones were synthesized and evaluated in the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), ferric reducing antioxidant power (FRAP), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays as a new chemotype with antioxidant and good drug-like properties. All of the derivatives showed low cytotoxicity in comparison to curcumin against the human neuroblastoma SH-SY5Y and the human hepatoma HepG2 cell lines. Experimental solubility in bio-relevant media showed a good relationship with melting points in this series. Five compounds with the best antioxidant properties showed neuroprotectant activity against H2O2-induced oxidative stress in the SH-SY5Y cell line. From them, derivatives 4-phenyl-1H-1,5-benzodiazepin-2(3H)-one (18) and 4-(3,4,5-trimethoxyphenyl)-1H-1,5-benzodiazepin-2(3H)-one (20) yielded good neuroprotection activity in the same neuronal cell line under 6-OHD and MPP+ insults as in vitro models of mitochondrial dysfunction and oxidative stress in Parkinson's disease (PD). Both compounds also demonstrated a significant reduction of intracellular Reactive Oxygen Species (ROS) and superoxide levels, in parallel with a good improvement of the Mitochondrial Membrane Potential (ΔΨm). Compared with curcumin, compound 18 better reduced lipid peroxidation levels, malondialdehyde (MDA), in SH-SY5Y cells under oxidative stress pressure and recovered intracellular glutathione synthetase (GSH) levels. Apoptosis and caspase-3 levels of SH-SY5Y under H2O2 pressure were also reduced after treatment with 18. Neuroprotection in neuron-like differentiated SH-SY5Y cells was also achieved with 18. In summary, this family of 1,5-benzodiazepin-2-ones with an interesting antioxidant and drug-like profile, with low cytotoxic and good neuroprotectant activity, constitutes a new promising chemical class with high potential for the development of new therapeutic agents against PD.